Cárie e dor dentária: fatores associados em pacientes acometidos por coagulopatias hereditárias no estado da Paraíba - Rodrigues, Larycia Vicente (2013)
There are few studies on the oral health status of patients suffering from bleeding disorders and factors associated with caries and dental pain. This study aimed to determine a probabilistic model that represents the likelihood of the event and Pain Dental Caries occurs in patients affected by inherited bleeding disorders in the state of Paraíba, by applying the Logistic Regression. Methodology: Epidemiological survey transversal, descriptive and inferential statistics, using a quantitative approach. Data on the oral health status were collected by an examiner previously calibrated blood centers in Paraíba, one located in João Pessoa and Campina Grande in another, during the months of October/2011 to July/2012. Information relating to socioeconomic, demographic, utilization of dental services, dental morbidity, self-perception of oral health and hygiene behavioral habits were obtained through semi-structured questionnaire and analyzed by means of logistic regression, being presented through statistical descriptive and inferential. Results: We observed high prevalence of caries, registering average dmft 6.00 for children between 1-5 years and mean DMFT of 6.36 for the age group of 13-19 years. He noted, too, the cumulative pattern of decay between 20-35 years of age (DMFT = 11.5) and of 36-59 (DMFT = 20.04). Most patients reported no pain in the last 6 months prior to the survey (73.6%). Were identified as protective factors for dental caries the shortest distance where the individual resides to reach the blood center where he makes treatment (OR = 1.89) and be patient with severe hemophilia A (OR = 6.09), whereas age (OR = 1.13) and the assertion that there is a need for dental treatment (OR = 5.76) were identified as risk factors. As for dental pain, it was observed that when looking for a dentist for the last time due to pain (OR = 26.7), feel uncomfortable with your teeth to brush them (OR = 7.3) and having difficulty with health professional other than the dentist (OR = 3.7) were considered as risk factors. However, if the patient has mild hemophilia A, the chances decrease (OR = 4.6), and is therefore a protective factor. Conclusion: Patients affected by bleeding disorders due to deficiency of coagulation factors present in the state of Paraíba a significant prevalence of caries, mainly recording the cumulative nature of this disease, denotes the fact that these individuals lack access to oral health care. The coagulopatas with older age and who reported needing dental treatment have higher risk of tooth decay, as well as those who have difficulties with health professionals, who only seek dental service for reasons of pain and bother to brush your teeth tend to present risks for dental pain. It is suggested that decision-making strategies prioritize health promotion and prevention of injuries through integration with health services at the primary level, with municipal health departments and state, continuing investigations and submitting the interventions to be instituted to constant evaluation.